Reading Motivation in Kindergartners and 1st-Graders. Issue 4 (2nd October 2019) - Nevo, Einat; Vaknin-Nusbaum, Vered; Gambrell, Linda
ABSTRACT: The current research examined age differences and developmental aspects associated with children's early motivation to read at the beginning and the end of the school year for 119 Hebrew speakers in kindergarten and 1st grade. Analyses showed that overall motivation to read was higher among 1st-graders than among kindergartners. In addition, motivation to read increased during the school year for kindergartners, but not for 1st-graders. After comparing the three motivational subscales, results revealed that self-concept as a reader appeared to be the highest subscale among 1st-graders and remained unchanged, whereas in kindergarten it was the lowest and improved during the school year. It is possible that both anticipation to enter 1st grade and to learn to read as well as learning in an encouraging educational environment might be positive motives that contribute to reading motivation. Children's motivation to read seems to develop and change during the kindergarten school year and consolidate in 1st grade. Motivational aspects should be assimilated as early as kindergarten before formal reading instruction begins in 1st grade to increase reading motivation and reading practice, due to their reciprocal relationship.